Functional Oversight Reform as a Strategic Instrument for Effective Regional Financial Governance - Saprudin, Saprudin; Abdul Radjak Masjhur, Mohamad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study examines functional oversight reform as a strategic instrument to strengthen regional financial governance in Bone Bolango Regency, Gorontalo Province. The research is motivated by weak internal control systems and limited inspectorate capacity, which often trigger irregularities in financial management. Employing a descriptive qualitative approach with a case study design, data were gathered through in-depth interviews with key informants the Inspector of Bone Bolango Regency, three auditors, and two supporting staff supported by observations and document analysis. The analysis identifies five core themes. First, functional oversight reform through the Government Internal Control System SPIP, shifting supervision from reactive to preventive. Second, financial governance strategies emphasizing risk-based auditing and the creation of task forces within OPD. Third, the use of information technology to enhance transparency, efficiency, and real time risk mapping, though constrained by infrastructure and human resources. Fourth, the role of organizational culture, especially integrity, professionalism, and participatory leadership, in sustaining effective oversight. Fifth, community involvement via the whistleblowing system and the WASKITA Clinic, which strengthens accountability despite low participation. The study contributes theoretically by emphasizing the interplay of structural, cultural, and technological factors in determining the effectiveness of public sector oversight. From a policy standpoint, it highlights the need for stronger governmental commitment to empower inspectorates as internal supervisory bodies (APIP), enhance digital infrastructure, improve human resource competence, and expand public literacy on financial monitoring. These policy implications aim to build a more adaptive, accountable, and transparent financial oversight system that supports sustainable regional governance.